Piperacillin-tazobactam fixed dose combination induced skin reaction in a patient with split thickness skin grafting: a case report - Solanki, Vaibhav; Sinha, Anita; Rathva, Trushti; Kanjariya, Dilip (International Journal of Basic & Clinical Pharmacology, 2024)
Piperacillin is a semi-synthetic ureido-penicillin. It has a broad spectrum against gram negative bacilli particularly P. aeruginosa. It is one of the most broadly active of the currently available penicillin with regard to other bacterial species like proteus, klebsiella, H. influenzae and gonococci. Tazobactam is β-lactamase inhibitor and combined with piperacillin to increase spectrum of the drug. Patient was 25 years old female, admitted in orthopaedic department for treatment of traumatic leg injury of left limb. Leg was amputated in the accident, so after 1-month split thickness skin grafting was done at plastic surgery department. For prophylaxis piperacillin-tazobactam IV 4.5 gm 8 hourly given, on 2nd post operative day patient reported rashes on neck, trunk, both upper and lower extremities, sparing the mucous membrane. Patient was prescribed anti pruritic and anti-allergic medication for ADR management. It is necessary to use such kind of drugs cautiously in patients whose health is deteriorated by this medication.